ความวิตกกังวลและปัจจัยที่เกี่ยวข้องกับความวิตกกังวลในการหางานทำของนิสิตปริญญาตรีชั้นปีสุดท้าย จุฬาลงกรณ์มหาวิทยาลัย - ปิยะพรรณ เอื้ออริยะพานิชกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this cross-sectional descriptive study was to explore the level of anxiety and its associated factors regarding job application among senior undergraduate students of Chulalongkorn University. Four hundred senior undergraduate students who would not like to find jobs after graduation and would not study in Master degree or already have reserved work. The research instruments were a demographic questionnaire, questionnaire about causes of anxiety of job application and questionnaire anxiety of job application. The data were analyzed using descriptive statistics, independene t – test, one-way ANOVA, pearson correlation and multiple linear regression analysis where appropriate. The results showed mean and SD regarding the anxiety of job application score were 58.9 and 12.96 respectively. The possible score range from 25-125. When using standard Mean +- 1 SD to set the level of the anxiety of job application, 15.5 % of the population sample had high level of anxiety, with score higher than 72. Factors associated with increased anxiety of job application were being female, incompetence in English and discrepancy between the job and the major subject studies. The implications of these finding by related institutions should promote psychological heath and prevent problems of senior undergraduate students and can be used properly to manage the anxiety of job application among senior undergraduate students.